Intertidal benthic red algae (Rhodophyta) from Essaouira coastline (Morocco) - Hasnae Sabri; Ricardo Haroun; Nadia Bahammou; Mustapha Hasni; Younes Boundir; Abdelmalek Maarouf; Ouafa Cherifi (Egyptian Journal of Aquatic Research, 2021)
The taxonomic information about macroalgal species along the Atlantic coast of Morocco is sparse and, in most cases, related to historical records. The aim of the present study is to catalogue the subtidal and intertidal red seaweeds inhabiting three coastal areas nearby Essaouira city, extended between 31° 52′ N−9° 75′ W North and 31° 49′ N −9° 76′ W South. It is the first revised and updated checklist of Rhodophyceae for almost 18 years on the Atlantic Moroccan coastline. A total of 196 taxa belonging to 104 genera was recorded, with an increase of 22% in species compared to previous studies. Additionally, the new benthic macroalgal species collected in the different seasons of the year are shown as well as a comparative analysis of the Ecological State Groups (ESG) of the new records with their Recovery Index (RI) among the three sampled coastal areas.